The Reality of the Application of the Quality of Work life in Public Hospitals During Corona Pandemic A Field Study in Tartous city - رشا حمدوش (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to show the extent of the application of the quality of work life in public hospitals in Tartous city. To achieve the objectives of the study, the descriptive analytical approach was followed, through a questionnaire distributed to the study sample, which consisted of (320) employees with all their functional specializations (technical, administrative, nursing, medical) in the public hospital within Tartous city, and it was received by hand and entered to the statistical analysis program ((SPSS25)), and conducting tests for the research sample in addition to testing hypotheses, and the most important findings of the research are the following: There is an acceptance application of the quality of work life in general and in public hospitals in Tartous city, and its most important items revolve around the moral working conditions, job groups, job characteristics, wages and rewards, and method of supervision . The results of the descriptive analysis of the study sample showed that there is a high level of the quality of work life in terms of moral working conditions, job groups and job characteristics in the public hospitals under study. The results of the descriptive analysis of the study sample showed a low level of quality of work life in terms of wages and rewards in the public hospitals under study. The results of the descriptive analysis of the study sample showed that there is an average level of the quality of work life in terms of the method of supervision in the public hospitals under study.